2022
DOI: 10.1039/d1fo02218k
|View full text |Cite
|
Sign up to set email alerts
|

Bifidobacterium lactis BL-99 protects mice with osteoporosis caused by colitis via gut inflammation and gut microbiota regulation

Abstract: Patients diagnosed with inflammatory bowel disease or related conditions also frequently suffer from osteoporosis as a consequence of changes in the intestinal microenvironment and consequent dysbiosis. We hypothesized that anti-inflammatory...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 75 publications
(86 reference statements)
0
18
0
Order By: Relevance
“…As an indispensable part of OP, the bone health and PMOP of middle-aged and elderly women is of particular concern [ 41 ]. Currently, accumulating evidence suggests that GM dysbiosis is involved in the pathogenesis and clinical manifestations of PMOP [ 19 , 42 ]. In this current study, our data suggested that FMT treatment could reshape the status of GM and ameliorate the bone loss in mice with OVX-induced OP.…”
Section: Discussionmentioning
confidence: 99%
“…As an indispensable part of OP, the bone health and PMOP of middle-aged and elderly women is of particular concern [ 41 ]. Currently, accumulating evidence suggests that GM dysbiosis is involved in the pathogenesis and clinical manifestations of PMOP [ 19 , 42 ]. In this current study, our data suggested that FMT treatment could reshape the status of GM and ameliorate the bone loss in mice with OVX-induced OP.…”
Section: Discussionmentioning
confidence: 99%
“…It was isolated from the intestinal tract of a healthy Chinese infant and has been reported to ameliorate colitis and its associated osteoporosis. 19 There is evidence that DSS-induced colitis mice have inflammatory factors and inflammatory cell infiltration in the lungs. 20 In our previous study, we also observed lung pathological damage and a decrease in lung function in UC mice.…”
Section: Introductionmentioning
confidence: 99%
“…[17]. In addition, the homeostatic gut microbiome community serves the host via a wide range of physiological activities, including digesting food [18,19], preventing pathogens [20], maintaining the function and integrity of the intestinal epithelial layer [21,22], and modulating the host immune system [23][24][25]. With the assistance of advanced bioinformatics and machine learning artificial intelligence, strong links have been identified between the gut microbiota and many human diseases [26], such as diabetes [27], irritable bowel disease [28], and autism [29].…”
Section: Introductionmentioning
confidence: 99%